Not Getting Out While There Is Still Time? Behavioral Response to Threat as a Possible Mechanism of Sexual Revictimization - (:unkn) unknown (My University, 2014)
Sexual violence affects approximately one in four college women. Feminist sexual assault risk reduction programs attempt to empower women to cope with threats of sexual assault, yet there is no standardized way to assess behavioral responses to threat, the key behavior targeted in these interventions. In this study, we sought to compare the behavioral responses of two groups of college women, those without a history of any sexual victimization, n = 12 and those with a history of repeated sexual victimization, n = 45 in a standardized analog task in order to investigate possible group differences which may lead to increased risk for sexual assault and psychological factors which facilitate different styles of responding. Results indicate that women with a history of victimization were more likely to engage in less effective behavioral response styles. Hierarchical regression analyses found that interpersonal skills predicted assertive style responding. These findings indicate this analog task may be useful as a risk assessment to identify those in need of risk reduction intervention and that women with a history of sexual assault may require greater or different kinds of intervention in order to reduce risk. Finally, results indicate interpersonal skills as a possible target for increasing the efficacy of risk reduction interventions.
Keywords: Assessment; Behavioral Response; Rape; Self-Defense; Sexual Assault